Flipped Classroom in Islamic Higher Education: Learning Readiness and Self-Regulated Learning among Islamic Religious Education Students - Retno Try Purnawati; Indra Fajar Nurdin; Mahmud Arif; Muhammad Nur Najimi (Universitas Sebelas Maret, 2026)
Learning in higher education still faces challenges in the form of low learning readiness and student learning independence, especially in the Islamic Religious Education Study Program (PAI). Students tend to be passive and depend on lecturers as the main source of knowledge so that the learning process has not been optimally student-centered. This study aims to analyze the application of Flipped Classroom in PAI students, analyze the dynamics of learning readiness, and explore the development of student learning independence during the application of this method. The research uses a qualitative approach with an analytical descriptive type. The research subjects were six students of the fourth semester PAI Study Program who took the Tarikh Tasyri' course through the Flipped Classroom model, selected using the purposive sampling technique. Data collection was carried out through triangulation techniques that included passive participatory observation, in-depth interviews, and documentation. Data analysis refers to the interactive model of Miles, Huberman, and Saldaña through the stages of data condensation, data presentation, and conclusion drawn, and its validity is guaranteed through triangulation techniques and member checking. The results of the study showed that the Flipped Classroom makes a positive contribution to student learning readiness through four Slameto indicators, namely physical condition, mental condition, emotional condition, as well as needs, motives, and goals. In addition, student learning independence develops through Zimmerman's three stages of self-regulated learning, namely forethought, performance, and self-reflection. Thus, Flipped Classroom contributes to encouraging PAI students to be more active, ready, and independent in the learning process.